HUBUNGAN POLA BERMAIN GADGET DENGAN KEMAMPUAN KOGNITIF DAN BERPIKIR KREATIF PADA ANAK USIA PRASEKOLAH (5-6 TAHUN) DI TK MUSLIMAT NU 10 AL-HIDAYAH MALANG - Nurmahidayati, Intan; Keswara, Nila Widya; Wijayanti, Tut Rayani Aksohini (NHM PRESS, 2024)
The positive impact of playing gadgets is related to the process of cognitive development, development of symbolic representation, development of attention, opportunity and understanding of essence, faster clear classification, decision making, analysis, cause and effect relationships, memory development, encouraging creativity, encouraging curiosity, developing imagination. problem solving processes, and increasing motivation. The type of research used in this research is analytical observational using a cross sectional approach where researchers will carry out observations or measurements of variables at the same time. The population in this study were all students aged 5-6 years in classes Kindergarten A and Kindergarten B at TK-Muslimat Al-Hidayah Kepanjen, totaling 46 people. The sample technique uses purposive sampling. The number of samples in this study was 32 people who were divided into two groups of equal size. The research results showed that most respondents had good gadget playing patterns. Most respondents have cognitive abilities in the good category. Most respondents have creative thinking in the good category. There is a relationship between gadget playing patterns and cognitive abilities in preschool children (5-6 years) at Muslimat Al-Hidayah Malang Kindergarten with a P value of 0.000 < 0.05. There is a relationship between gadget playing patterns and creative thinking in preschool children (5-6 years) at the Muslimat Al-Hidayah Malang Kindergarten with a P value of 0.000 < 0.05.